Katya a cinematic essay on the anting-anting belief of the Ilonggo Land Grabbers Association (ILAGA) - Nietes, Stephanie Camille D. (2018)
The Ilonggo Land Grabbers Association or ILAGA is a group in Mindanao known for their belief in the anting-anting which they call Katya. A cinematic essay was utilized to create an insightful discourse and articulate the belief of the ILAGA on Katya and its relationship with the concept of loob and power. The film explored the conventions of the cinematic essay: the visuals and spoken essay. These conventions showed the interpretive and subjective imagery of the ILAGA and Katya. The production thesis shared viewpoints regarding the cinematic essay, the history of ILAGA and the discourses on the beliefs in anting-anting of the said group. In order to flesh out the nuances about the Katya and the ideas on loob and power, two frameworks are considered: concept on ?Pagkataon Pilipino? of Prospero Covar from his article: Kaalamang Bayang Dalumat ng Pagkataong Pilipino? (1993), and the developing framework for Philippine studies on ?loob? of Reynaldo Ileto from his book Pasyon and Revolution Popular Movements in the Philippines (1979). The concepts provided by the two frameworks served as the backbone of the production thesis.